ANALISIS TERMODINAMIKA SIKLUS HIBRID UNTUK PEMBANGKIT LISTRIK TENAGA PANAS BUMI - Astina, I Made; Kurniawan, Kadek Edy; Pastalozi, Merly (Mesin, 2008)
Modification of the conventional cycle in a geothermaL power plant is an alternative way that can be conducted in efficient conversion of thermal energy to be electric energy. Combination of Brayton cycle with fossil fuel energy sources and Rankine cycle utilizing geothermal energy is interest of this study. Kamojang Geothermal power plant is chosen as an object of casestudy. A software was developed to accurately evaluate the thermodynamic cycle with any modification. The software is supported by thermodynamic properties database directly derived from equations of state. Hybrid cycle analysis was conducted by comparing the conventional geothermal system operating with independent Rankine cycle such as the current Kamojang geothermal power plant in accordance with rational data ernd assumptions.Simulation results show that 157.88% of power increment, 58.17% of efficiency increment for using organic working fluid R-134a. Replacing R-134a with organic working R-600 afford 162.89% of power increnrent and 63.76% of efficiency increment. Ratio of the net power increment respect to the heating input of fuel is 0.52. This high enhancement is achieved for gas turbine inlet temperature of 1100 celcius degree, pressure ratio of 20, gas temperatltre front steam heater at 350 celcius degree, steam temperature from the heater at 250 celcius degree, and organic turbine inlet pressure and temperature at 35 bars and 340 celcius degree, respectively.